Screening for NPHS2 mutations may help predict FSGS recurrence after transplantation - Jungraithmayr, Therese; Hofer, Katrin; Cochat, Pierre; Chernin, Gil; Cortina, Gerard; Fargue, Sonja; Grimm, Paul; Knüppel, Tanja; Kowarsch, Andreas; Neuhaus, Thomas; Pagel, Philipp; Pfeiffer, Karl P.; et al. (Journal of the American Society of Nephrology, 2011)
Steroid-resistant focal segmental glomerulosclerosis (FSGS) often recurs after renal transplantation. In this international survey, we sought to identify genotype-phenotype correlations of recurrent FSGS. We surveyed 83 patients with childhood-onset primary FSGS who received at least one renal allograft and analyzed 53 of these patients for NPHS2 mutations. The mean age at diagnosis was 6.7 years, and the mean age at first renal transplantation was 13 years. FSGS recurred in 30 patients (36%) after a median of 13 days (range, 1.5 to 152 days). Twenty-three patients received a second kidney transplant, and FSGS recurred in 11 (48%) after a median of 16 days (range, 2.7 to 66 days). None of the 11 patients with homozygous or compound heterozygous NPHS2 mutations developed recurrent FSGS compared with 45% of patients without mutations. These data suggest that genetic testing for pathogenic mutations may be important for prognosis and treatment of FSGS both before and after transplantation.
Gesehen am 06.07.2022